(untitled) (Experimental biology, 2019)
The topic of research is the current direction of modern experimental oncology - the problem of studying the role of autophagy in the survival and death of a cancer cell. The purpose of this work was to study the cell heterogeneity of the hepatocarcinoma-29 population and the development of autophagy as a way of surviving tumor cells. The scientific significance of the work lies in obtaining previously unknown facts about the development of basal autophagy in certain types of hepatocarcinoma cells, which is a way of surviving tumor cells. The novelty of this study is to identify the types of hepatocarcinoma cells in which the process of autophagy develops, contributing to the survival of the tumor cell population and obtaining data on the structural features and activity of the autophagy process.The practical significance of the work lies in the possibility of using the obtained data for the development of targeted therapy of hepatocarcinoma through the combined use of inducers of autophagy and cytostatics, which will simultaneously use different cellular signaling pathways to stimulate apoptosis and autophagic cell death. The work was performed on the culture of hepatocarcinoma -29 cells using light and electron microscopy. The heterogeneity of the population of cells was revealed, which is determined by the size of the cells and the volume fraction of the nucleus and cytoplasm. In terms of cell volume and nuclear-cytoplasmic ratio, five types of cells are distinguished, corresponding to five stages of differentiation. In the IV and V cells of the differentiation stages, autophagic structures were revealed: autophagosomes, autolysosomes, and lysosomes. The findings make a significant contribution to cell biology, cytology and histology, as well as oncology. Key words: hepatocarcinoma-29, heterogeneity, stages of cell differentiation, autophag